IoT in social science education: Bridging theory and practice for interdisciplinary connections - Azizan Had; Starry Garijih (Indian Academicians and Researchers Association, Guwahati, 2023)
In this extensive paper, we delve into the profound impact of the Internet of Things (IoT) on the intersection of theoretical frameworks in social science and their practical manifestations. The focus of this study is to explore the potential of incorporating IoT technologies into social science education, emphasising the bridging of the gap between theoretical concepts and practical applications. Through IoT devices and platforms, educators in social science can establish interdisciplinary connections, providing students with real-world experiences that deepen their comprehension of intricate social phenomena. The paper thoroughly discusses the advantages and challenges associated with integrating IoT in social science education, offering concrete examples of successful implementations and proposing strategies for educators to incorporate IoT into their curriculum seamlessly. Overall, this paper contends that IoT can revolutionise social science education, equipping students for the increasingly interconnected world they will navigate post-graduation. The article scrutinises educators’ perceptions regarding integrating IoT into social science education. Their insights highlight the potential of IoT to stimulate student engagement, critical thinking, and problem-solving skills, all while acknowledging challenges such as data privacy concerns and financial constraints. The paper also unravels the interdisciplinary landscape of IoT-enhanced learning experiences by examining real-world examples. These IoT-infused experiences cultivate a holistic understanding of social science concepts across diverse academic disciplines by immersing students in hands-on, experiential learning. The conclusion positions the IoT ecosystem as a powerful catalyst, propelling education and social science research into an era of innovation, collaboration, and profound interdisciplinary connections. The narrative consistently underscores the transformative role of IoT, shaping the future trajectory of education and social science research.